Digital Forensics in Ghana: A Decade of Legal Insights - Yunita Makhfudotin, Hana; Multazam, Mochammad Tanzil; Hasan, Rizqi (Proceedings of The ICECRS, 2023)
In this data article, we aimed to streamline research endeavors in the field of digital forensics within the context of Ghana by retrieving relevant literature. We initiated the search on Lens.org with the keyword "Digital Forensic," coupled with "Ghana," yielding a total of 238 documents. Subsequently, we employed filters to refine the dataset, focusing on journal articles, narrowing down the publication years to the past decade (2012-2022), and specifying the subject matter as "Law," resulting in 12 documents. The data collected serves as a valuable resource for researchers, facilitating a comprehensive literature review, and promoting in-depth studies on the intersection of digital forensics and Ghana. This dataset offers insights, methods, and results essential for a better understanding of the subject, aiding future studies in this domain.Highlights : Comprehensive Data: The dataset encompasses a decade's worth of digital forensic research in Ghana, providing a valuable resource for scholars. Legal Focus: The filtered data specifically pertains to the legal aspects of digital forensics, offering insights into the intersection of law and technology. Streamlined Research: Researchers can efficiently conduct literature reviews and studies on digital forensics in Ghana using this refined dataset. Keywords: Digital Forensic, Ghana, Legal Perspective, Research Resource, Decade Analysis